2014
DOI: 10.1002/ca.22429
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the extensor digitorum communis tendon and its insertion variants: A systematic review and meta‐analysis

Abstract: The tendons of the Extensor Digitorum Communis (EDC) are frequently injured in hand trauma. Dislocation and spontaneous rupture can also occur during the course of wrist osteoarthritis and rheumatoid arthritis. The EDC exhibits many variations including splitting of its individual slips to the medial four fingers or their absence. The aim of this systematic review is to assemble evidence about the prevalence of the EDC and its variants on the dorsum of the hand. Twenty-four cadaveric studies met the inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The EDM tendon is frequently used in the case of an abduction deformity of the little finger. Its variations were reported by Yammine (2014). Li and Mao (2014) reported an EDM with five slips on the right hand.…”
Section: Variations Of the Posterior Compartmentmentioning
confidence: 86%
See 1 more Smart Citation
“…The EDM tendon is frequently used in the case of an abduction deformity of the little finger. Its variations were reported by Yammine (2014). Li and Mao (2014) reported an EDM with five slips on the right hand.…”
Section: Variations Of the Posterior Compartmentmentioning
confidence: 86%
“…Anatomical variations of the finger extensor tendons are not uncommon and have been described by several authors (ABDEL-HAMID, EL-BESHBISHY and ABDEL AAL, 2013; BETTENCOURT PIRES, CASAL, MASCARENHAS DE LEMOS et al, 2013;BLUTH, WU, ELENA STARK et al, 2011;CASANOVA MARTINEZ, VALDIVIA GANDUR and GOLANO, 2013;CASANOVA-MARTINEZ, VALDIVIA-GANDUR and GOLANO, 2014;AVDAR and SEHIRLI, 1996;LI and MAO, 2014;MEHTA et al, 2009;NAYAK, HUSSEIN, KRISHNAMURTHY et al, 2009;NAYAK, KRISHNAMURTHY, PAI et al, 2008;NAYAR and MCARTHUR, 2009;RAY, RANADE, D'COSTA et al, 2010;ROY, MEHTA, SURI et al, 2010;YAMMINE, 2014YAMMINE, , 2015ZAINO, MITGANG, RAWAT et al, 2014). Some of these studies included anatomical variations of the first dorsal compartment of the wrist in relation to their importance in de Quervain's disease (NAYAK, HUSSEIN, KRISHNAMURTHY et al, 2009;ROY, ROY, DE et al, 2012;ROY, MEHTA, SURI et al, 2010).…”
Section: Variations Of the Posterior Compartmentmentioning
confidence: 98%
“…In this article, we introduced the CATAM rubric and used it to critically appraise a recently published anatomical MA (Kacprzyk et al, 2020). There have been other anatomical MAs recently published (Aldabe et al, 2019; Bellier et al, 2020; Berthaume & Bull, 2021; Cheruiyot et al, 2021; Dreher et al, 2018; Graves et al, 2017; Harvie et al, 2019; Koziej et al, 2020; Morelli et al, 2019; Nallikuzhy et al, 2018; Roberts et al, 2021; Sirico et al, 2019; Solewski et al, 2021; Stefura et al, 2018; Tomaszewska et al, 2018; Tomaszewska et al, 2018; Tomaszewski et al, 2017; Tomaszewski et al, 2017; Vikse et al, 2016a, 2016b; Whitley et al, 2020; Yammine, 2013, 2014b, 2014c, 2014d; Yammine et al, 2015; Yurasakpong et al, 2021). We believe that the running paper that we used is an exemplary anatomical MA (Kacprzyk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic variations and prevalence of the extensor muscle tendons have been reported in many studies (3,4). Similarly to these studies, in this case report, we showed rare variations of extensor carpi radialis brevis and extensor digitorum muscles.…”
Section: Introductionmentioning
confidence: 95%